Pola Pengasuhan Santri Asrama dalam Pembentukan Karakter di Pondok Pesantren Madrasatul Qur’an Al Muthawassithoh Jajar Islamic Center Surakarta - Winarno, Andhika Sarfatra (Asian Journal of Islamic Studies and Da'wah, 2024)
Islamic boarding schools are Islamic educational institutions, which have an important role in the history of education in Indonesia. Islamic boarding schools have a distinctive characteristic of education in Indonesia which is identical to the dormitory system. In Islamic boarding schools, the dormitory system makes it the role of educators to educate students with optimal discipline through the student care section. The role of the student care department is very strategic in planning, controlling, supervising and evaluating the entire process of activities and programs for 24 hours with a systemic approach and methods. This research aims to determine the parenting patterns of the Madrasatul Qur'an Al Muthawassithoh Islamic boarding school in shaping the character of its students. This research uses qualitative descriptive research, and data collection is carried out using interview, observation and documentation methods. And the informants for this research are the Caretaker, Senior Teacher at Madrasatul Qur'an Al Muthawassithoh son of Jajar Islamic Center Surakarta, the Islamic boarding school section, as well as the Islamic boarding school organization section, as well as several Islamic boarding school students. In this study, researchers found that the pattern of nurturing students is carried out systematically and structured by implementing management functions in the process of caring for students at the Madrasatul Qur'an Al Muthawassithoh Islamic boarding school (MQW) which includes direction, assignment, training, habituation, supervision, example (uswatun hasanah ), and the process of creating an environment with the totality of santri life for 24 hours through various boarding school activities and programs within the Islamic boarding school environment which move dynamically based on the educational values at the Jajar Islamic Center Islamic boarding school. Then, implement management patterns and schemes, part of nurturing students in forming the character of students through daily activities commonly carried out by students and extracurricular activities including sports, arts, leadership, self-development and entrepreneurship. Then among the supporting factors are the role and figure of a caregiver, the dormitory system and Islamic boarding school environment, and the inhibiting factors are the santri guardians, facilities and infrastructure, and knowledge about parenting.